Pengaruh Work-Life Balance Terhadap Employee Performance a Systematic Literature Review - Ahmad Bahrul Ulum; Elisabeth Supriharyanti (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to examine the effect of work-life balance (WLB) on employee performance through a systematic literature review approach. Work-life balance has become a strategic issue in human resource management, especially in facing the challenges of a dynamic modern work world. The results of the analysis indicate that work-life balance has a significant effect on employee performance, both directly and through mediators, such as job satisfaction, organizational commitment, and work motivation. In addition, it was found that the effect of work-life balance on employee performance can vary depending on the industry sector, work culture, and individual employee characteristics. This study contributes to the development of organizational policies by offering strategic insights into the importance of supporting work-life balance to improve employee performance. The findings also identify research gaps that can be further explored, especially in the context of cultural differences and work sectors.